Improvement of The Light Output of Blue InGaN-Based Light Emitting Diodes by Using a Buried Stripe-Type n-Contact and Reflective Bonding Pad. (1st January 2020) - Kim, Jong-Ho; Lee, Yong Won; Im, Hyeong-Seop; Oh, Chan-Hyoung; Shim, Jong-In; Kang, Daesung; Seong, Tae-Yeon; Amano, Hiroshi
Abstract : To enhance the light output of blue InGaN-based light emitting diodes (LEDs), a buried stripe-type n -electrode, expanded stripe-type p -electrode, and reflective p -bonding pad were employed. Flip-chip (FC) LEDs with the expanded p -electrode gave forward voltages of 2.99–3.11 V at 100 mA and series resistances of 3.28–3.94 Ω. The expanded p -electrode FCLED fabricated with 375 nm-thick window and TiO2 adhesion layers produced 22.7% higher light output at 21 A/cm 2 than conventional FCLEDs. The expanded p -electrode FCLEDs revealed better current spreading efficiency than the c-FCLED, indicating the importance of the use of an optimised window and TiO2 adhesion layers.